Streamlining Oral Antidiabetic Prescribing Through Clinical Pathway Implementation - Wardani, Susilo Ari (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Background: Diabetes mellitus (DM) is a disease that falls into the high-volume, high-risk, and high-cost categories. A concordance of oral anti-diabetic drug prescribing with the clinical pathway (Pedoman Praktik Klinis, PPK) will ensure drug availability for patients in the universal coverage era.Objectives: This study aimed to analyze the quantity and quality of antidiabetic drug use before and after PPK implementation, including concordance with the national formulary and PPK.Methods: This cross-sectional study analyzes oral antidiabetic drug use for inpatient DM (ICD-10 E11) at Sumberglagah Regional Hospital, Mojokerto, East Java Province, Indonesia. Data were collected retrospectively from medical records and the pharmacy database. Drug utilization was presented in Defined Daily Dose per 100 bed-days descriptively.Results: The quantity of inpatient DM drug use was 189.17 DDD/100 bed-days and 249.42 DDD/100 bed-days, before and after PPK implementation. The types of DM drugs that were included in the 90% DU category, before and after PPK implementation, were Insulin Aspart, Insulin Glargine, Glimepiride tablets, and Insulin Glulisine. The quality of DM drug use was 100% following the National Formulary 2022 and the PPK.Conclusion: The oral anti-diabetic drugs in the 90% drug cumulative have great attention in the procurement to raise the financial efficiency. The DDD/100 bed-days of anti-diabetic and the number of items of anti-diabetic drugs are increasing, therefore necessitates proactive strategies to manage potential cost escalation for payers, i.e., The Government of Republic Indonesia.